Edukacja w epoce współczesnych kryzysów - Morbitzer, Janusz (Studia Edukacyjne, 2020)
Morbitzer Janusz, Edukacja w epoce współczesnych kryzysów [Education in the Era of Contemporary Crises]. Studia Edukacyjne nr 56, 2020, Poznań 2020, pp. 7-26. Adam Mickiewicz University Press. ISSN 1233-6688. DOI: 10.14746/se.2020.56.1 The article shows that the educational process is always carried out in a complex, multidimensional world and its competent description requires consideration of many contexts, which also include numerous crises. The essence of a crisis is presented and such selected crises: ecological, socio-cultural, intellectual, and educational (including the crisis of universities) are described and briefly characterized. Their interpenetration and impact as well as influence on the educational process are demonstrated.